Fusarium Head Blight Resistance QTL in the Spring Wheat Cross Kenyon/86ISMN 2137 - McCartney, Curt A.; Brûlé-Babel, Anita L.; Fedak, George; Martin, Richard A.; McCallum, Brent D.; Gilbert, Jeannie; Hiebert, Colin W.; Pozniak, Curtis J. (Frontiers in Microbiology, 2016)
Fusarium head blight (FHB), caused by Fusarium graminearum, is a very important disease of wheat globally. Damage caused by F. graminearum includes reduced grain yield, reduced grain functional quality, and results in the presence of the trichothecene mycotoxin deoxynivalenol in Fusarium-damaged kernels. The development of FHB resistant wheat cultivars is an important component of integrated management. The objective of this study was to identify QTL for FHB resistance in a recombinant inbred line (RIL) population of the spring wheat cross Kenyon/86ISMN 2137. Kenyon is a Canadian spring wheat, while 86ISMN 2137 is an unrelated spring wheat. The RIL population was evaluated for FHB resistance in six FHB nurseries. Nine additive effect QTL for FHB resistance were identified, six from Kenyon and three from 86ISMN 2137. Rht8 and Ppd-D1a co-located with two FHB resistance QTL on chromosome arm 2DS. A major QTL for FHB resistance from Kenyon (QFhb.crc-7D) was identified on chromosome 7D. The QTL QFhb.crc-2D.4 from Kenyon mapped to the same region as a FHB resistance QTL from Wuhan-1 on chromosome arm 2DL. This result was unexpected since Kenyon does not share common ancestry with Wuhan-1. Other FHB resistance QTL on chromosomes 4A, 4D, and 5B also mapped to known locations of FHB resistance. Four digenic epistatic interactions were detected for FHB resistance, which involved eight QTL. None of these QTL were significant based upon additive effect QTL analysis. This study provides insight into the genetic basis of native FHB resistance in Canadian spring wheat.